The Effects of Isoflurane and Desflurane on Cognitive Function in Humans - Zhang, Bin; Tian, Ming; Zhen, Yu; Yue, Yun; Sherman, Janet; Zheng, Hui; Li, Shuren; Tanzi, Rudolph E.; Marcantonio, Edward R.; Xie, Zhongcong (Anesthesia and analgesia, 2012)
The etiology of postoperative cognitive decline (POCD) remains to be determined. Anesthetic isoflurane, but not desflurane, may induce neurotoxicity. However, the functional consequences of these effects have not been assessed. We therefore performed a pilot study to determine the effects of isoflurane and desflurane on cognitive function in humans. The subjects included patients who had lower extremity or abdominal surgery under spinal anesthesia alone (S, n = 15), spinal plus desflurane anesthesia (SD, n = 15), or spinal plus isoflurane anesthesia (SI, n = 15) by randomization. Each of the subjects received cognitive tests immediately before and 1 week after anesthesia and surgery administered by an investigator who was blinded to the anesthesia regimen. POCD was defined using the scores from each of these tests. We studied 45 subjects, 24 males and 21 females. The mean age of the subjects was 69.0 ± 1.9 years. There was no significant difference in age and other characteristics among the treatment arms. The mean number of cognitive function declines in the S, SD, and SI groups was 1.13, 1.07, and 1.40, respectively. POCD incidence after SI (27%), but not SD (0%), anesthesia was higher than that after S (0%), P = 0.028 (3-way comparison). These findings from our pilot study suggest that isoflurane and desflurane may have different effects on postoperative cognitive function, and additional studies with a larger sample size and longer times of follow-up testing are needed.